Accent boundaries and linguistic continua in the laryngeal subsystems of English - Balogné Bérces, Katalin (LingBaW. Linguistics Beyond and Within, 2022)
A parallel is drawn between the northernmost regions of England represented by Durham and Yorkshire and the transition zone Ouddeken (2016) identifies between voicing and aspiration languages in the Dutch-German dialect continuum. It is argued that, owing to historical changes and dialect contact, the Northern Englishes discussed exhibit hybrid laryngeal systems as a result of being geographically intermediate between Scots in Scotland, which is a voice language similar to Dutch, and mainstream varieties of English spoken more to the south in England (and in most of the rest of the English-speaking world), which are aspiration systems of the German type. We model the emergence of laryngeal systems as the setting of three parameters: (i) whether the laryngeally marked/specified obstruent series contains [voice] (L-system) or [asp] (H-system); (ii) whether the laryngeal prime is able to spread (right-to-left); and (iii) whether the system has pre-obstruent delaryngealisation (POD) (due to which in C1C2, C1 becomes unmarked/underspecified). While spreading L with POD derives voice languages and non-spreading H with no POD derives aspiration languages, two mixed combinations derive the intermediate categories of Durham and Yorkshire (spreading L & no POD and spreading H & no POD, respectively). We also show that all remaining combinations are attested cross-linguistically or else theoretically uninterpretable.